Representasi Hatarakisugi pada Tokoh Aoyama Takashi dalam Film Chotto Ima Kara Shigoto Yamete Kuru karya Izuru Narushima - Kitai, Taro (KIRYOKU, 2024)
This research is titled "The representation of hatarakisugi on the character Aoyama Takashi in the movie Chotto Ima Kara Shigoto Yamete Kuru by Izuru Narushima. This research focuses on showing the representation of hatarakisugi and the impact of hatarakisugi on the character Aoyama Takashi in the movie Chotto Ima Kara Shigoto Yamete Kuru. The method used in this research is descriptive qualitative method, the data source of this research is the movie Chotto Ima Kara Shigoto Yamete Kuru. The theories used are literary psychology theory by Wellek and Warren, literary sociology theory by Damono, and semiotics theory by Danesi. Based on the results of the study, it is known that the representation of hatarakisugi that occurs in the character Aoyama Takashi includes; 1) a wrong mindset; 2) neglecting personal health; and 3) forcing oneself to overwork. The positive and negative impacts of hatarakisugi on the character Aoyama Takashi in the movie Chotto Ima Kara Shigoto Yamete Kuru (2017) by Izuru Narushima. The positive impacts are; 1) fostering an unyielding attitude; 2) fostering a high discipline attitude; and 3) daring to make decisions. While the negative impacts are; 1) decreased motivation; 2) stress; 3) Depression; and 3) suicidal thoughts.